UPLC/Q-TOF MS-based femoral muscle metabolomic analysis under high-temperature: a proof of concept for postmortem interval estimation - Chen, Yinyu; Zheng, Gaolin; Yang, Xinyan; Zhang, Peng; Nie, Qianyun (Frontiers in Medicine, 2025)
IntroductionAccurate postmortem interval (PMI) estimation is a major challenge in forensic medicine, especially for the rapidly and highly putrefied bodies in tropical high-temperature areas. Despite numerous studies, there are still no reliable, objective methods to accurately estimate PMI for corpses found in a high-temperature environment.MethodsIn the current research, an ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF MS)-based metabolomics approach was employed for the analysis of the metabolic profile of rat femoral muscle tissue in a high-temperature environment at different postmortem intervals. Multivariate pattern recognition and pathway analyses were employed for the identification of differential metabolites.ResultsThis study identified 14 significantly changed metabolites and two altered metabolic pathways. Among them, L-threonine, histidyl-threonine, L-tryptophan, N6-acetyl- L-lysine, eicosapentaenoic acid, glycerol 3-phosphate, and creatine were selected as possible diagnostic biomarkers for PMI estimation. Their impact value and potential biological function in the organisation’s degradation process were the basis for selection.DiscussionThis study demonstrated the feasibility of UPLC/Q-TOF MS-based metabolomics in femoral muscle tissue research and identified several differential metabolites that may provide forensic scientists with a helpful reference in PMI estimation in a high-temperature environment.